Civics Education at Schools: Problems and Challenges - Muñoz Labraña, Carlos (2014)
This article reports the results of a research project financed by the Chilean Ministry of Education (FONIDE No. 310894) and the Center for Advanced Research in Education (AEIC) (FONDAP No. 11-2009).  The aim of this research project was to investigate the students’ perception regarding civics education, which, according to school curricula, should be taught in school, in order to detect the problems and challenges resulting from those perceptions, which will be faced by history and geography teachers in schools.  The methodology used was qualitative and phenomenological.  Samples were selected using an intentional sampling method and included male and female eighth graders from twelve schools from different administrative units in the Concepción district in Chile.  Information was obtained using a thorough semi structured interview and analyzed using the Atlas.ti Software.  Results were not very promising since, despite the Ministry’s recent efforts, which included changes made during the last decade to civics education, students do not have an adequate notion of what civics education is or what it is for.  Neither do they consider these classes a space that helps them in this respect.